Serum apolipoproiein b-100 concentrations in periparturienl diseases of dairy cows - Turan Civelek; Mutlu Sevinç (Eurasian Journal of Veterinary Sciences)
The purpose ol this study was to examined the changes ol serum apolıpoproteın B-100 concentrations and to evaluate Ihe liver I unction in penparturienl diseases for dairy cows. In this study. 9 healthy and 36 diseased (18 abomasum displacement, 9 primary kelosis and 9 reiensio secundrnarum), totaly 45 dairy cows were used. Serum concent rations of glucose, cholesterol, triglyceride, tola! pıoteın. albumin, AST, GGT and HDL were measured enzimatically. VLDL and LDL were calculated by formula. And also Ihe concentrations ol serum apolıpoprotein B-100 were assayed by single radial im-munodilkısıon method Hepatic biopsy samples were obtained Irorn liver under local anesthesia with percutaneous biopsy needle In this research, it was concluded lhat serum HDL, LDL. VLDL. total cholesterol, triglyceride (p=0 001) and total protein (p=0.002) also albumin (p=0 028) levels were slgnilicanlly decreased, and AST (p=0.001), GGT (p=0.012) and total bilirubin (p=0.005l levels significantly increased in cows wilh abornasai displacement compared to healthy cows. The liver biopsies from cows wilh abomasal displacement had %43.27+3.l7 (severe fally liver) lat mlillration. In pnmary ketosis fjioup scrum HDL LDL. VLDL. total cholesterol, triglyceride, glucoso (p=0.00l) and total proiem (p=0.003) a;so albumin tp=0 009) levels were significantly decreased, however AST, GGT and total bilirubin (p=0.001 i significantly increased compared lo healthy cows. The liver biopsies from cows with pnmary kelosis had %48.89±8 09 (severe fatty liver) (at migration. In cows with retained placenla compared lo healthy cows serum HDL. LDL, VLDL, total cholesterol, tnglycoride (p=0.001) and glucose (p=0.002) also total protein (p=0.005) levels were signilicantly decreased, but AST (p=0.002) slgnilicanlly increased. The liver biopsies Irom cows wilh retained placenta had %36.89±7.75 (moderate fatty liver) fal infiltration. Also sorum apo B-100 conconlralions were signilicantly decreased in cows with displaced abomasum (p=0.001). primary ketosis (p=0.006) and retained placenta (p=0.016) compared to healthy cows Our resulls indicated mat apo 8-100 is an useful indicator lor diagnosis and evaluation ot penpartunenı diseases in dairy cows Individual changes in apo B-100 concentrations should be interpreted carelully like the other parameters.